MANAJEMEN KEARSIPAN DALAM MENINGKATKAN EFISIENSI, KEAMANAN INFORMASI, DAN KUALITAS LAYANAN PENDIDIKAN DI ERA DIGITAL - Brilia Rahmawati; Cunita Pujiya Restari; M. Zidni Ilman Nafian; Ngilma Uswatun Solimah; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Records management plays a crucial role in supporting effective governance in educational institutions, especially in the digital era characterized by rapid technological advancements. This study aims to analyze the role of records management in improving efficiency, information security, and the quality of educational services. The research employs a qualitative approach using literature review and document analysis techniques. The findings indicate that the implementation of digital records management systems enhances the speed of information retrieval, minimizes data loss risks, and improves transparency and accountability. Additionally, the use of technologies such as electronic document management systems and cloud storage contributes to information security through controlled access and data backup mechanisms. Effective records management also improves the quality of educational services by ensuring that information is accessible quickly, accurately, and reliably. Therefore, digital-based records management has become a strategic necessity for educational institutions in addressing the challenges of the digital era. Keywords: records management, efficiency, information security, educational services, digital era